Atherosclerosis : risks, mechanisms, therapies - Wang, Hong, 1956 September 19-; Patterson, Cam (Wiley Blackwell, 2014)
Comprehensive and in-depth in its coverage, Atherosclerosis: Cellular, Molecular & Biochemical Mechanism and Novel Therapy reviews the recent progress in atherosclerosis research and offers cutting edge perspectives from experts in the field. Written by an international team of authors including leading physician-scientists, research experts and physicians, chapters are divided into four major sections, covering risk factors, cellular and molecular mechanisms, biochemical mechanisms and novel and future therapeutics. Atherosclerosis: Cellular, Molecular & Biochemical Mechanism and Novel The.